An endoglycosidase with alternative glycan specificity allows broadened glycoprotein remodelling. - Goodfellow, J; Baruah, K; Yamamoto, K; Bonomelli, C; Krishna, B; Harvey, D; Crispin, M; Scanlan, C; Davis, B (2012)
Protein endoglycosidases are useful for biocatalytic alteration of glycans on protein surfaces, but the currently limited selectivity of endoglycosidases has prevented effective manipulation of certain N-linked glycans widely found in nature. Here we reveal that a bacterial endoglycosidase from Streptococcus pyogenes , EndoS, is complementary to other known endoglycosidases (EndoA, EndoH) used for current protein remodeling. It allows processing of complex-type N-linked glycans +/- core fucosylation but does not process oligomannose- or hybrid-type glycans. This biocatalytic activity now addresses previously refractory antibody glycoforms.